Learning to heal : reflections on nursing school in poetry and prose - Bryner, Jeanne, 1951-; Davis, Cortney, 1945-; Schaefer, Judy (Literature and medicine (Kent, Ohio), 2018)
"Fifty nurses discuss various aspects of student nursing and provide historical perspective on nursing and nursing education through personal essays and poems"--